DEVELOPMENT OF PRIVATE ENTREPRENEURSHIP IN UZBEKISTAN (Conferencea, 2023)
The article aims to provide an overview of the development of private entrepreneurship in Uzbekistan and the various measures taken by the government to promote it. It also examines the impact of these measures on the country's economy, and discusses the challenges and future prospects for the sector.